Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1155/2017/6823965
|View full text |Cite
|
Sign up to set email alerts
|

Axial Length and Ocular Development of Premature Infants without ROP

Abstract: Purpose To investigate the ocular parameters of premature infants without ROP at gestational age (GA) more than 28 weeks and their relationship with growth parameters. Methods 76 preterm infants without ROP and 65 term infants were involved to undergo portable slit lamp, RetCam3, ultrasonic A-scan biometry, and cycloplegic streak examination at their 40 weeks' postconceptional ages (PCA). Ocular parameters of infants' right eye and growth parameters were used for analysis. Results All the infants were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…27 But even without ROP premature infants have a shorter axial length: Zha demonstrated a significant difference between children born at 33 weeks and term infants both measured at 40 weeks gestational age (17.08 ± 0.67mm vs 17.34 ± 0.55mm), and Fledelius stated that axial length in premature eyes does not catch up with the growth of full-term eyes, even by 18 years of age. 10,39 Premature newborns also have been described to be more myopic than term controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 But even without ROP premature infants have a shorter axial length: Zha demonstrated a significant difference between children born at 33 weeks and term infants both measured at 40 weeks gestational age (17.08 ± 0.67mm vs 17.34 ± 0.55mm), and Fledelius stated that axial length in premature eyes does not catch up with the growth of full-term eyes, even by 18 years of age. 10,39 Premature newborns also have been described to be more myopic than term controls.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,11,13,28,30,39 Anthropometric parameters such as birth weight (Blomdahl, Denis, Stafford, O'Brien&Clark, Zha), crown-heel and crown-rump length (Denis, Stafford), and orbitofacial parameters such as head circumference (Stafford, O'Brien and Clark, Zha) are suggested to be potentially correlated. 3,7,26,34,39 Contrarywise, Pennie found no correlation between birth weight and axial length. 28 Trivedi found an ethnic difference not confirmed in other studies where African-American infants had significantly longer eyes than Caucasian infants (21.66mm versus 20.14mm).…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been shown that birth weight is more correlated with refractive error in preterm babies compared to gestational age (9,10). Similarly, Varghese at al.…”
Section: Discussionmentioning
confidence: 85%
“…Searching for a possible difference in ocular morphology and visual acuity in the CH group, we have found lower values in ACD, ACV, and HCD in the eutopic gland subgroup compared to patients with the ectopic gland. The lower gestational age of eutopic subgroup can show these results: in fact, although the literature contains several conflicting reports [15,16], according to some researches [17][18][19][20] birth parameters (gestational age, birth weight, birth length, and birth head circumference) have a lasting effect on ocular dimensions in adolescence and adulthood. Finally, the higher frequency of refractive errors in our athyreotic subgroup could have a certain importance but the small numerosity of study population has not allowed us to deduce a reliable conclusion.…”
Section: Discussionmentioning
confidence: 99%